2012
DOI: 10.1111/gcbb.12001
|View full text |Cite
|
Sign up to set email alerts
|

Co‐generated fast pyrolysis biochar mitigates green‐house gas emissions and increases carbon sequestration in temperate soils

Abstract: Char is a product of thermochemical conversion of biomass via pyrolysis, together with gas (syngas), liquid (bio-oil), and heat. Fast pyrolysis is a promising process for bio-oil generation, which leaves 10-30% of the original biomass as char. Char produced for soil application, is defined biochar (BC), and it may increase soil C storage, and reduce soil emissions of greenhouse gases (GHG), such as N 2 O and CH 4 -potentially making fast pyrolysis bioenergy generation a C-negative system. However, differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(114 citation statements)
references
References 55 publications
5
107
1
1
Order By: Relevance
“…Positive (Luo et al, 2011), negative (Cross and Sohi, 2011) and unchanged effects (Santos et al, 2012) of biochar addition on the mineralization rate of the native SOC had been found. These inconsistent effects might be due to differences in biochar feedstock, pyrolysis temperature, or soil type (Stewart et al, 2013). Luo et al (2011) reported a shortterm positive priming effect of biochar addition on SOC mineralization, when biochar was produced from Miscanthus giganteus at 350 C. On the other hand, Lu et al (2014) found a negative priming effect with biochar produced from corn straw.…”
Section: Introductionmentioning
confidence: 99%
“…Positive (Luo et al, 2011), negative (Cross and Sohi, 2011) and unchanged effects (Santos et al, 2012) of biochar addition on the mineralization rate of the native SOC had been found. These inconsistent effects might be due to differences in biochar feedstock, pyrolysis temperature, or soil type (Stewart et al, 2013). Luo et al (2011) reported a shortterm positive priming effect of biochar addition on SOC mineralization, when biochar was produced from Miscanthus giganteus at 350 C. On the other hand, Lu et al (2014) found a negative priming effect with biochar produced from corn straw.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a fine-grained carbonaceous solid residue, produced by pyrolysis of carbon-rich biomass under oxygen-limited conditions (Chen et al 2011;Xu et al 2013). In recent years, biochar has also received considerable interest as a large-scale soil amendment to enhance crop productivity and soil fertility (Major et al 2010;Vaccari et al 2011;Farrell et al 2014;Prayogo et al 2014;Song et al 2014), to increase soil water holding capacity (Kammann et al 2011;Baronti et al 2014), to decrease nutrient leaching (Laird et al 2010), and to serve as a recalcitrant carbon stock (Lehmann 2007a, b;Laird 2008) to potentially mitigating climate changes Cimò et al 2014) by reducing greenhouse gas emissions Stewart et al 2013). Biochar has many properties, such as a relatively structured carbon matrix, high degree of microporosity, extensive surface area, and high pH and cation exchange capacity (CEC); therefore, it may act as a surface adsorbent (Jiang et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Pedological analyses revealed a decrease of soil pH in the order superphosphate > SS > BC A + SS > BC B + SS > BC A > BC B for both application rates. An increase of soil alkalinity following biochar amendment has been reported for many soil types (FARRELL et al, 2014;STEWART et al, 2013;XU et al, 2013). As mentioned before, this effect is due to the alkaline character of biochar because of the presence of negatively charged phenolic, carboxyl and hydroxyl functional groups on surfaces (BREWER et al, 2012).…”
Section: Effect Of Soil Amendments Incorporationmentioning
confidence: 74%